Consensus scoring-guided virtual screening identifies potent anti-saprolegniasis compounds targeting a P450 fusion protein - Ali, Muhammad Akhtar; Javaid, Anum; Muvva, Charuvaka; Arul Murugan, Natarajan; Srivastava, Vaibhav (Frontiers in Microbiology, 2026)
Saprolegniasis, predominantly caused by Saprolegnia spp., particularly Saprolegnia parasitica, has reemerged as a major threat in aquaculture, resulting in substantial economic losses of millions of dollars annually. Historically, malachite green was highly effective against this disease; however, its use was banned in aquaculture due to its carcinogenic nature. Consequently, there is an urgent need for novel and effective agents to mitigate economic losses. Several studies, including a subtractive-proteomics study from our laboratory, have identified multiple anti-saprolegnia compounds; however, their efficacy remains to be confirmed in vivo. Targeting mitochondrial energy production in Saprolegnia offers a potential strategy to combat this pathogen. Notably, cytochrome P450 is unique to Saprolegnia species and was previously shown to be inhibited by malachite green. In this study, we performed a virtual screening of FDA-approved drugs to identify compounds that target P450 and thereby disrupt energy production. To ensure robust ranking of potential inhibitors, we integrated multiple docking tools and applied consensus scoring. Based on ranking and water solubility, selected compounds were subjected to in vitro testing. Among these, chlorhexidine and diminazene exhibited strong anti-saprolegnia activity in liquid culture, with MIC₅₀ values of 10.93 and 417 μg/ml, respectively. Although chlorhexidine was less potent than malachite green, it demonstrated substantial inhibitory activity at low microgram per milliliter concentrations, highlighting its potential as a promising candidate for further development in aquaculture.